The what and where of primate field research may be failing primate conservation. Issue 4 (25th July 2019) - Bezanson, Michelle; McNamara, Allison
Abstract: With approximately 30% of nonhuman primate species listed as critically endangered, the window of opportunity to conserve primates is closing fast. In this article, we focus on the degree to which publications in field primatology are biased in favor of particular taxa and field sites. We examined more than 29, 000 peer‐reviewed articles and identified 876 field visits to 349 field sites. We found a highly clumped distribution by site and species. We also examined publication ethical statements and the extent to which they acknowledged local human communities (<5%). Due to a lack of consistency across publications, we provide recommendations for improving ethical statements and for evaluating research impact. Given the plight of primate biodiversity, these results suggest broader coverage of primate species and geographies, as well as more attention to the local human communities whose support is necessary if the intent is to have primate species in the wild in the 22nd century.